Iraqi Nurses' Perspectives on Safety Issues in Maternity Services - Jamil Piro; Ghiyasvandian; Salsali (Kashan University of Medical Sciences, 2015)
Background Studies introduce maternal and neonatal safety phenomena as important challenges to the public health, particularly in low-income countries. However, few researches are conducted on the identification of safety issues in maternity hospitals in Iraq. It was the first study on nurses' perspectives on safety issues in Kurdistan, Iraq. Objectives The current study aimed to describe nurses' perspectives on what constitutes a safe maternity service in Kurdistan, Iraq. Patients and Methods A qualitative design, based on a content analysis approach, was used. Ten Kurdish nurses who worked in the delivery room of Kurdistan, Iraq maternity hospital were recruited through purposive sampling. Semi-structured interviews were performed to collect data. All interviews were audiotaped and transcribed verbatim. Sampling continued to the level of data saturation. Data analysis was performed based on the steps suggested by Graneheim and Lundman. Results Thematic analysis led to the identification of six main categories including stressful job, lack of schedule and job description, providing care with limited resources, professional unaccountability, regional sociopolitical factors, and inadequate training. Conclusions Iraqi nurses identified factors such as limited health resources, lack of job description, and professional unaccountability as major safety issues in maternity services. These findings alarm the need to ensure the provision of females and neonates with appropriate care. This, however, would require coordination between Iraqi Kurdistan health authorities to provide midwifery care facilities, high-quality and relevant staff training, and an effective healthcare system in the maternity units.